Immunosuppression and apoptosis activation mediated by p53-Bcl2/Bax signaling pathway -The potential mechanism of goldfish (Carassius auratus Linnaeus) gill disease caused by Myxobolus ampullicapsulatus - Liu, Senyue; Luo, Lin; Zuo, Fengyuan; Geng, Yi; Ou, Yangping; Chen, Defang; Yang, Shiyong; Luo, Wei; Wang, Yan; Wang, Jun; Huang, Xiaoli (Frontiers in Immunology, 2022)
Myxobolus, a major harmful type of myxospora, is one of the main parasitic pathogens of freshwater fish. Once myxoboliosis occurs, treatment can be extremely difficult. Therefore, clear understandings of the etiology of myxoboliosis and its pathological mechanism are keys for prevention and control. Here, histology, transmission electron microscopy, transcriptome study, tunel assay, and immunohistochemistry were carried out, revealing the morphology, pathological effects as well as host response mechanism of goldfish gill to Myxobolus ampullicapsulatus. Histological studies showed that the mature spores of Myxobolus ampullicapsulatus were composed of three parts, the spore shell, sporoplasm and bottle shaped polar capsule containing double S-shaped polar filaments. Transcriptome analysis revealed that Myxobolus ampullicapsulatus -infected (Myx) goldfish gills were characterized by apoptosis activation mediated by "p53 signaling pathway" with significantly up-regulated apoptosis-related differential genes dominated by p53-Bcl2/Bax signaling pathway. In addition, tunel assay revealed severe gill apoptosis in the Myx group. Transcriptome analysis also revealed that Myx group showed changes in immune response and significantly down-regulated immune-related differential genes. Beyond that, immunohistochemistry showed that there was no significant increase in the number of gill lymphocyte after parasite infection. These results suggest that the pathological mechanism of Myxobolus ampullicapsulatus infection on gills of goldfish may be related to apoptosis and immunosuppression. Subsequent qRT-PCR showed that apoptosis-related genes (Caspase3 ,Bad, Bax) and anti-inflammatory gene IL-10 were significantly increased, while immune-related pro-inflammatory genes (IL-1β, IL-8) were markedly down-regulated, further verifying the transcriptome results. Based on the above results, we concluded that p53-Bcl2/Bax related networks that dominant the expression of apoptosis genes were activated while immunity was suppressed in the gills of Myxobolus ampullicapsulatus infected goldfish. Our study is not only of benefit to enrich the taxonomy of Myxobolus but also clarifies its pathogenic mechanism, thus providing targets for prevention and control of myxoboliosis.